Daily liver rhythms: Coupling morphological and molecular oscillations - Ueli Schibler; Flore Sinturel; Felix Naef; Alan Gerber; David Gatfield (Proceedings of the National Academy of Sciences, 2025)
In mammals, a hierarchically organized circadian timing system orchestrates daily rhythms of nearly all physiology. A master pacemaker in the brain’s suprachiasmatic nucleus (SCN) synchronizes subsidiary clocks in most peripheral organs. By driving anabolic and catabolic cycles of proteins, lipids, and carbohydrates and by detoxifying endo- and xenobiotic components, the liver plays an important role in adapting the metabolic needs to rest-activity rhythms. In keeping with these functions, the liver expresses many clock-controlled genes that are required for these processes. Remarkably, however, this organ also fluctuates in size and morphological parameters. In mice, the mass of the liver increases and decreases by 30 to 40% during the 24-h day. The oscillation in liver mass is accompanied by daily rhythms of similar amplitudes in hepatocyte cell size and global RNA and protein accumulation. The number of ribosomes, which parallels the ups and downs of liver size, appears to be the rate-limiting factor in driving the diurnal rhythms of overall protein synthesis. Obviously, the rapid increase in hepatocyte size within the liver engenders mechanical stress, which must be dealt with by increasing the physical robustness of cells. Indeed, the actin cytoskeleton of hepatocytes undergoes dramatic polymerization cycles. Thus, massive intracellular and subcortical F-actin bundles are assembled during the night, at which the liver reaches its maximal size. In turn, the oscillation in actin polymerization elicits rhythms in myocardin-related transcription factors-serum response factor signaling, which participate in the circadian transcription of the core clock gene Per2 and thereby contribute to the synchronization of hepatocyte clocks.